PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS QUANTUM TEACHING DENGAN PENDEKATAN SCIENTIFIC PADA TOPIK HIMPUNAN KELAS VII SMP - ROMA WINARTA (Jurnal Edukasi dan Penelitian Matematika, 2021)
This study aims to produce a product in the form of a quantum teaching-based student worksheet with a scientific approach that is valid and practical for students of class VII SMPN 4 Padang. This type of research is design research using the Plomp development model which consists of three stages, namely Preliminary Research, Prototyping Phase, and Assessment Phase. The preliminary research stage includes needs analysis, curriculum analysis, student analysis, and analysis of teaching materials. Prototyping phase is the stage for designing student worksheets based on quantum teaching with a scientific approach consisting of prototype 1, prototype 2, and prototype 3 which are evaluated using a formative evaluation design. The instruments used in this development research were interview guidelines, observation sheets, questionnaires and final tests. The results showed that student worksheets based on quantum teaching with scientific approach that is valid and practical.Keywords – Student worksheets, Quantum Teaching, scientific approach, Valid, Practical